EVALUASI PROGRAM EKSTRAKURIKULER REBANA DI SD NEGERI BENER 01 MENGGUNAKAN MODEL COUNTENANCE STAKE - Rahmawati, Mely; Astuti, Suhandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to evaluate the rebana extracurricular program at SD Negeri Bener 01 using the Countenance Stake model, which includes antecedents, transactions, and outcomes aspects. This study used a qualitative descriptive approach with the principal, extracurricular coach, and rebana students as the research subjects. Data were collected through observation, interviews, and questionnaires. The results showed that the antecedents aspect obtained 100% in the very good category, supported by competent coaches, adequate facilities, and clear program objectives. The transactions aspect obtained an observation percentage of 80% in the good category and a questionnaire result of 84% in the very good category. The outcomes aspect obtained an observation percentage of 100% and a questionnaire result of 91% in the very good category. The rebana extracurricular program positively impacted students’ musical abilities, discipline, cooperation, self-confidence, and religious values. Therefore, the rebana extracurricular program at SD Negeri Bener 01 has been implemented very well and supports students’ character development.